2014
DOI: 10.1039/c4ra05724d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of three-dimensional WO3 octahedra: characterization, optical and efficient photocatalytic properties

Abstract: First time synthesized novel WO3 octahedra exhibited photocatalytic performance of about 5.33 times than that of bulk which may be attributed to large surface area and highly reactive facet {120}.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The optical band gaps, E g , of all the three samples were calculated by the well-known equation used in ref. 24. The band gaps of CdWO 4 , WO 3 and WO 3 /CdWO 4 photocatalyst were estimated as 3.30, 2.77 and 2.97 eV respectively as can be seen from Fig.…”
Section: Optical Absorption Propertiesmentioning
confidence: 71%
“…The optical band gaps, E g , of all the three samples were calculated by the well-known equation used in ref. 24. The band gaps of CdWO 4 , WO 3 and WO 3 /CdWO 4 photocatalyst were estimated as 3.30, 2.77 and 2.97 eV respectively as can be seen from Fig.…”
Section: Optical Absorption Propertiesmentioning
confidence: 71%
“…The e − can participate in organic pollutant degradation reactions. The possible formations of the superoxide anion, hydroperoxyl, and hydrogen peroxide (H 2 O 2 ) species in the organic dye solution are advantageous for further degrading the MB dyes [21]. However, it has been shown that the position of the conduction band of WO 3 (+0.50 V vs. NHE) was below the standard redox potential for the formation of superoxide anion (−0.33 V vs. NHE) and hydroperoxyl (−0.046 V vs. NHE) [22].…”
Section: Resultsmentioning
confidence: 99%
“…Such variation may arise because of expansion of new doping levels in catalyst's lattice that could facilitate the efficient migration and transfer of an electron from VB to CB. The extended range of visible light absorption of prepared nanocomposite results in the formation of more charge carriers and hence enhanced photocatalytic activity for hydrogen production . The formation of the charge carriers on photocatalyst's surface because of variation of E g value has advantageous to enhanced photocatalytic performance.…”
Section: Resultsmentioning
confidence: 99%